Analyzing the COVID-19 parameters for large Brazilian municipalities using a model with fuzzy transitions between epidemic periods - Lima, Hélder Seixas; Guimarães, Frederico Gadelha (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2024: Anais do XXIV Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas.2024.1874, 2024)
This study investigates the dynamics of the COVID-19 pandemic across the 41 largest Brazilian municipalities from 2020 to 2022. We used a mathematical model with fuzzy transitions between epidemic periods to estimate epidemiological parameters such as basic reproduction number (R0) and the Infection Fatality Rate (IFR). We provide insights into the trajectory of the pandemic by correlating these parameters with data on social isolation, vaccination efforts, and the emergence of new variants. Our findings highlight the role of social isolation in reducing R0 in 2020 and the impact of mass vaccination on lowering the IFR in 2022. However, the highest mortality rates recorded in 2021 underscore the complex interplay of various factors observed in that moment.